Indicators of Innovation Climate in Russia (Results of Mass Population Surveys) - Olga Shuvalova (Foresight and STI Governance)
Сontemporary innovation policies are based mostly on the results of statistical and sociological studies for companies and expert surveys. However, the problem of motivating innovation activity is unlikely to be solved without taking into consideration the peculiarities of people’s attitude to science, technology and education, which can be identified as areas which provide a basis for innovative development. The author analyses the views of general public about technologies, competitiveness, prestige of S&T occupations, allied government policies and prospects of innovation. The results of representational studies of public awareness of S&T and Innovation implemented in Russia and elsewhere were used to perform this analysis.